A Mapping of Environmental Mitigation Measure along the Propose Access Road in Reserve Forest Using Drone Technology - Adand, Amirul Izzad; Ridzuan, Mohd Baharudin (Recent Trends in Civil Engineering and Built Environment, 2021)
Basically, soil erosion is know to be a massive challenge to land depletion that has impacted soil nutrients, carbon recycling, land productiveness and generated bad influences on construction. Therefore, Best Management Practices (BMPs) can prevent the loss of soil and reduce the land degradation. Besides, Unmanned Aerial Vehicles (UAVs) or define as drones have been commonly used by engineers or contractors as an effective method for engineering survey, excavation monitoring and historic landmark operations. As the technology has advanced and cost reduces, wide areas can be captured at high resolution and drones are now a typical part of engineering tools as this equipment can improve precision, speedy data collection and performance in the field of engineering. Meanwhile, constructed road at the reserved forest may cause the environmental impacts and pollution will be occurs at the site. This study was conducted to determine a suitable mitigation measure and to plot topography map for the access road in reserved forest using a drone at Bentong, Pahang. The method used to determine the suitable mitigation measure and topography map are by using a drone. Data were analyzed using software application which is Auto-CAD and Microsoft Excel Worksheet. The result shows that the objectives are obtained. The determination to plot the topography map by using drone technology can be achieved. Lastly, suitable mitigation measure along the propose access road will be compute by using BMPs.